Liberatory Anti-Oppression in Counselor Education: Infusing Action into Pedagogy - Fleitas, Karli; Evans, Amanda; Palacios, Alfredo; Kress, Victoria (ILIN Education Indonesia, 2025)
In higher education, the experiences of historically marginalized and underrepresented students are often undervalued, challenged, or ignored. Counselor educators must actively advocate within predominantly white, heteronormative, and cisgender-centered training environments by leading initiatives that decolonize the classroom and center liberation. The purpose of this manuscript is to introduce, Liberatory Anti-Oppression in Counselor Education, a culturally responsive pedagogical framework designed to infuse anti-oppressive, antiracist, and liberation-based practices into counselor training. To develop this framework, we conducted a review of peer-reviewed scholarly literature from academic journals. The result of this inquiry is a structured approach for counselor educators to implement liberatory practices in the classroom. We conclude by calling for a shift in the counseling profession toward liberation, offering practical strategies for educators and students alike.